IMPACT ANALYSIS OF UTILIZING DIGITAL PAYMENT METHODS ON THE DEVELOPMENT OF IKAT WEAVING BUSINESSES IN KUPANG CITY - Klaasvakumok J. Kamuri; Irience R. A. Manongga; Andrias U. T. Anabuni; Yanti S. Giri (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to examine the influence of digital marketing and influencer endorsements on consumer purchase intentions, with trust as a moderating variable. Using a quantitative approach with a sample of 96 Kedaita consumers, data were collected through structured questionnaires and analyzed using multiple regression and moderation analysis. The findings indicate that both digital marketing and influencer endorsement have a positive impact on purchase intention. Moreover, trust strengthens the relationship between the independent variables and purchase intention, indicating its essential role in enhancing the effectiveness of promotional strategies. The results provide us a deeper understanding of how trust functions within digital marketing dynamics, particularly for small businesses. However, the confinement of this study to a specific regional context and consumer segment may limit the generalizability of the results. Future research is suggested to explore other moderating variables and apply broader population samples to validate and expand the insights. Keywords: Digital Payment; Ikat Weaving; Busniness Development